Analisis Return Saham Sebelum dan Sesudah Merger dan Akuisisi Pada Perusahaan Perbankan yang Terdaftar dI BEI Periode 2018-2022 - Defriani, Hartika; Hambani, Susy; Anwar, Saeful (Politeknik Raflesia Press, 2024)
Return is a method often used by investors in comparing investment alternatives which is used to show market reactions to merger and acquisition activities carried out by companies which affect the share prices of both the acquiring company and the target company. From the data obtained, it shows that these expectations have not been met because of stock returns. still shows small results. This research aims to determine the market reaction to mergers and acquisitions which is characterized by the average abnormal return value of majority shares around the date of merger and acquisition activity and to determine the difference in average abnormal stock returns before and after mergers and acquisitions in listed banking companies. on the IDX for the 2018-2022 period. This research method is descriptive analysis with a quantitative approach and the population in this research is banking companies listed on the Indonesia Stock Exchange and carrying out merger and acquisition activities in 2018-2022. Sampling was carried out using the Purposive Sampling method. The results of the research show that there is no market reaction to mergers and acquisitions as indicated by the average value of the majority of abnormal stock returns being significant around the date of the merger and acquisition and there is no difference in the average abnormal stock return between before and after the merger and acquisition.